Hbr's year in business and technology 2021 (2 books) - Review, Harvard Business. (Harvard Business Review Press, 2020)
The biggest technology and management ideas of the year, all in one place. This collection of the top ideas, insights, and best practices from the past year of Harvard Business Review will keep you up-to-date on the most cutting-edge, influential thinking driving business today. The two-book set brings together HBR's 10 Must Reads 2021 and The Year in Tech 2021: The Insights You Need from Harvard Business Review. The Must Reads volume assembles the definitive articles on topics in including leadership, strategy, and innovation from HBR's vast array of experts. The Insights book will help you understand today's most essential thinking on fast-moving technologies, and they mean for your organization. Together these books will equip you to successfully lead your business today as you prepare to reinvent your company for the future.